A Retrospective Comparative Study of Modified Percutaneous Endoscopic Transforaminal Discectomy and Open Lumbar Discectomy for Gluteal Pain Caused by Lumbar Disc Herniation - An, Junyan; Zhang, Jun; Yu, Tong; Wu, Jiuping; Nie, Xinyu; He, Tao; Yun, Zhihe; Liu, Rui; Xue, Wu; Qi, Le; Li, Yingzhi; Liu, Qinyi (Frontiers in Surgery, 2022)
Introduction This study aimed to demonstrate the safety and effectiveness of modified percutaneous endoscopic transforaminal discectomy (PETD) in the surgical management of single-segment lumbar disc herniation (LDH) gluteal pain and to determine whether it provides a better clinical outcome than open lumbar discectomy (OD). Methods A retrospective analysis of patients treated with modified PETD and OD for gluteal pain in LDH from January 2015 to December 2020 was conducted. Sample size was determined using a priori power analysis. Demographic information, surgical outcomes including procedure time (minutes), intraoperative blood loss (ml), hospital days, costs (RMB), fluoroscopy shots, recurrence and complications, etc., were recorded and analyzed. Prognostic outcomes were assessed using the visual analog scale (VAS), the Oswestry Disability Index (ODI), the Japanese Orthopedic Association Score (JOA) and modified MacNab criteria. The preoperative and postoperative VAS, ODI and JOA scores were recorded by two assistants. When the results were inconsistent, the scores were recorded again by the lead professor until all scores were consistently recorded in the data. MRI was used to assess radiological improvement and all patients received follow-ups for at least one year. Results The sample size required for the study was calculated by a priori analysis, and a total of 72 participants were required for the study to achieve 95% statistical test power. A total of 93 patients were included. In the modified PETD intragroup comparison, VAS scores ranged from 7.14±0.89 preoperatively to 2.00±0.58, 2.68±0.70, 2.55±0.69, 2.23±0.81, and 1.85±0.72 at 7 days, 1 month, 3 months, 6 months, and 12 months postoperatively. Patients showed significant pain relief postoperatively (p<0.01). According to the modified MacNab score, the excellent rate in the PETD group was 89.36%. There was no significant difference compared to the OD group (89.13%, P>0.05). Conclusion Modified PETD treatment is safe and effective for gluteal pain due to L4/5 disc herniation and has the advantages of a lower complication rate, faster postoperative recovery, shorter length of stay, fewer anesthesia risks and lower cost of the procedure compared with OD. However, modified PETD has a higher recurrence rate.